Characterization of Adults With a Self-Diagnosis of Nonceliac Gluten Sensitivity. (August 2014) - Biesiekierski, Jessica R.; Newnham, Evan D.; Shepherd, Susan J.; Muir, Jane G.; Gibson, Peter R.
Background : Nonceliac gluten sensitivity (NCGS), occurring in patients without celiac disease yet whose gastrointestinal symptoms improve on a gluten-free diet (GFD), is largely a self-reported diagnosis and would appear to be very common. The aims of this study were to characterize patients who believe they have NCGS. Materials and Methods : Advertising was directed toward adults who believed they had NCGS and were willing to participate in a clinical trial. Respondents were asked to complete a questionnaire about symptoms, diet, and celiac investigation. Results : Of 248 respondents, 147 completed the survey. Mean age was 43.5 years, and 130 were women. Seventy-two percent did not meet the description of NCGS due to inadequate exclusion of celiac disease (62%), uncontrolled symptoms despite gluten restriction (24%), and not following a GFD (27%), alone or in combination. The GFD was self-initiated in 44% of respondents; in other respondents it was prescribed by alternative health professionals (21%), dietitians (19%), and general practitioners (16%). No celiac investigations had been performed in 15% of respondents. Of 75 respondents who had duodenal biopsies, 29% had no or inadequate gluten intake at the time of endoscopy. Inadequate celiac investigation was common if the GFD was initiated by self (69%), alternative health professionals (70%), general practitioners (46%), or dietitians (43%). In 40 respondents who fulfilled the criteria for NCGS, their knowledge of and adherence to the GFD were excellent, and 65% identified other food intolerances. Conclusions : Just over 1 in 4 respondents self-reporting as NCGS fulfill criteria for its diagnosis. Initiation of a GFD without adequate exclusion of celiac disease is common. In 1 of 4 respondents, symptoms are poorly controlled despite gluten avoidance.